Developmental differences in family supervision of child injuries. (1st March 2011) - Piotrowski, C C; McRae, S; Stewart-Tufescu, A; Warda, L; Briggs, G; Tenenbein, M
Abstract : Objectives: The goal of the present study was to explore developmental differences in the nature of typical supervision by family members from infancy to adolescence. Methods: A phone survey was conducted in Winnipeg Manitoba Canada. Qualifying respondents were parents of a child up to 17 years of age living in the home. Parents were questioned about their typical supervision behaviours (ie, checking on their child) as well as whether a specific injury event occurred within the past 12 months. Results: Four hundred respondents were interviewed; of these, 88% reported having a child who sustained an injury within the past 12 months. Examination of injury cases indicated significant developmental differences in typical parent supervision style across age. Parents were most vigilant in their supervision of the youngest children (under age 4) and school-aged children (aged 5–11), reporting seeing and hearing them virtually all of the time (98%). However, parents were significantly more likely to report indirect supervision strategies such as checking occasionally for children aged 12 years and older. Interestingly, supervision by siblings also showed clear developmental trends; sibling supervision was most likely to occur for shorter periods of time (1–4 h) with children aged 12–14 years. A small minority of families (4%) reported using sibling supervision for children under the age of 12. Conclusions: There were significant differences in typical family supervision style as a function of child age. Findings suggest supervision style is a modifiable risk factor which may inform future injury prevention strategies.